Dysfunction of inhibitory interneurons contributes to synaptic plasticity via GABABR-pNR2B signaling in a chronic migraine rat model - Zeng, Xiaoxu; Niu, Yingying; Qin, Guangcheng; Zhang, Dunke; Chen, Lixue (Frontiers in Molecular Neuroscience, 2023)
Background According to our previous study, the loss of inhibitory interneuron function contributes to central sensitization in chronic migraine (CM). Synaptic plasticity is a vital basis for the occurrence of central sensitization. However, whether the decline in interneuron-mediated inhibition promotes central sensitization by regulating synaptic plasticity in CM remains unclear. Therefore, this study aims to explore the role of interneuron-mediated inhibition in the development of synaptic plasticity in CM. Methods A CM model was established in rats by repeated dural infusion of inflammatory soup (IS) for 7 days, and the function of inhibitory interneurons was then evaluated. After intraventricular injection of baclofen [a gamma-aminobutyric acid type B receptor (GABABR) agonist] or H89 [a protein kinase A (PKA) inhibitor), behavioral tests were performed. The changes in synaptic plasticity were investigated by determining the levels of the synapse-associated proteins postsynaptic density protein 95 (PSD95), synaptophysin (Syp) and synaptophysin-1(Syt-1)]; evaluating the synaptic ultrastructure by transmission electron microscopy (TEM); and determining the density of synaptic spines via Golgi-Cox staining. Central sensitization was evaluated by measuring calcitonin gene-related peptide (CGRP), brain-derived neurotrophic factor (BDNF), c-Fos and substance P (SP) levels. Finally, the PKA/Fyn kinase (Fyn)/tyrosine-phosphorylated NR2B (pNR2B) pathway and downstream calcium-calmodulin-dependent kinase II (CaMKII)/c-AMP-responsive element binding protein (pCREB) signaling were assessed. Results We observed dysfunction of inhibitory interneurons, and found that activation of GABABR ameliorated CM-induced hyperalgesia, repressed the CM-evoked elevation of synapse-associated protein levels and enhancement of synaptic transmission, alleviated the CM-triggered increases in the levels of central sensitization-related proteins, and inhibited CaMKII/pCREB signaling via the PKA/Fyn/pNR2B pathway. The inhibition of PKA suppressed the CM-induced activation of Fyn/pNR2B signaling. Conclusion These data reveal that the dysfunction of inhibitory interneurons contributes to central sensitization by regulating synaptic plasticity through the GABABR/PKA/Fyn/pNR2B pathway in the periaqueductal gray (PAG) of CM rats. Blockade of GABABR-pNR2B signaling might have a positive influence on the effects of CM therapy by modulating synaptic plasticity in central sensitization.